PENERAPAN PRINSIP NON-REFOULEMENT DALAM KASUS PENGUNGSI ROHINGYA DI MALAYSIA - Jannah, Fajdrina Raudatul; Saeri, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The humanitarian crisis affecting the Rohingya ethnic group since 2017 has triggered a massive exodus to Southeast Asian countries, including Malaysia. Although Malaysia is not a party to the 1951 Refugee Convention or its 1967 Protocol, it remains a major destination due to geographic proximity, cultural affinity, and economic factors. Malaysia's non-accession to the international refugee legal regime raises a key question: to what extent is the principle of non-refoulement implemented in practice, and how does Malaysia weigh this principle when responding to the arrival of Rohingya refugees? This research aims to explore these issues by examining the country’s policy dynamics between 2017 and 2022. This study employs a qualitative method with a descriptive-analytical approach. Data were collected through literature review from various primary and secondary sources, including UNHCR reports, official Malaysian government documents, academic literature, and international media coverage. The theoretical framework is based on Guy S. Goodwin-Gill’s absolute state sovereignty approach, which explains how states maintain full control over their borders and migration policies. The findings indicate that Malaysia implements the non-refoulement principle de facto, including through deportation moratoria, cooperation with UNHCR, and limited access to basic services. However, such implementation remains inconsistent and largely dependent on situational administrative policies. In the absence of a clear domestic refugee law and amid limited coordination or burden-sharing at the ASEAN level, protection for Rohingya refugees in Malaysia remains fragile and unsustainable. Keywords: Non-Refoulement, Refugees, Rohingya, Malaysia